1939 Golden Gate International Exposition Island (Western Notion & Novelty Co.)
Official view of the 1939 Golden Gate International Exposition Island. In the immediate left foreground is a 110-foot causeway, serving as a boulevard approach from the San Francisco-Oakland Bay Bridge. At the right is Exposition Harbor. 1500 feet wide and 3400 feet long, which will be used for marine regattas.